The impact of special strength intervention in water on the flutter kicking performance in swimming - Mandzak, P.; Mandzakova, M.; Pavlikova, R. (Journal of Physical Education and Sport, 2020)
The aim of the research was to verify the vertical flutter kicks effectiveness included in the junior swimmers` training process (n = 11, height = 178.57 ± 7.12, weight = 72.06 ± 12.93, age 16.27 ± 0.70 years ). We assumed that this special exercise in the training process will improve the performance of swimmers, what will result in improved times and decreasing number of kicks in the 50-meter test using flutter kicking. At the same time, we investigated whether the impact of this training would be more obvious when arms were close to the body or stretched upwards during swimming. The experiment was conducted for five months from October 2017 to early March 2018. The results confirmed the statistical significance of the given training method in favor of the swimmers experimental group in the number of kicks as well as in the 50m FK performance with both stretched arms and arms close to the body. The effect of the method had impact on the 50m FK test with stretched arms (Z = -3.251 (p <0.05, r = 0.69 - great effect). The performance was improved and the number of kicks reduced.